Discovery of structurally distinct tricyclic M4 positive allosteric modulator (PAM) chemotypes. Issue 4 (15th February 2020) - Temple, Kayla J.; Long, Madeline F.; Engers, Julie L.; Watson, Katherine J.; Chang, Sichen; Luscombe, Vincent B.; Rodriguez, Alice L.; Niswender, Colleen M.; Bridges, Thomas M.; Conn, P. Jeffrey; Engers, Darren W.; Lindsley, Craig W.
Graphical abstract: Highlights: Discovery of novel 2, 3-dimethylimidazo[1, 2- a ]pyrazine-6-carboxamide-based M4 PAMs. Broad survey of diverse heterocyclic cores. Balanced human and rat M4 PAM potency with excellent CNS penetration. Abstract: This Letter details our efforts to develop new M4 PAM scaffolds with improved pharmacological properties. This endeavor involved replacing the 3, 4-dimethylpyridazine core with two novel cores: a 2, 3-dimethyl-2 H -indazole-5-carboxamide core or a 1-methyl-1 H -benzo[d][1, 2, 3]triazole-6-carboxamide core. Due to shallow SAR, these cores were further evolved into two unique tricyclic cores: an 8, 9-dimethyl-8H-pyrazolo[3, 4- h ]quinazoline core and an 1-methyl-1 H -[1, 2, 3]triazolo[4, 5- h ]quinazoline core. Both tricyclic cores displayed low nanomolar potency against both human and rat M4 .